2015
DOI: 10.1002/tea.21273
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of diverse learners playing life science video games: Interactions between game content, learning disability status, reading proficiency, and gender

Abstract: Extant research reports differential effects related to the efficacy of video games as a means to enhance science instruction. However, there are very few studies examining differences in learning outcomes across student-level independent variables. This study used multilevel modeling to examine the effects of three video game-enhanced life science units on the performance of 366 adolescent students from three middle schools in the central and western United States. The study included 18 life science classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 47 publications
(59 reference statements)
0
15
0
6
Order By: Relevance
“…Moreover, Sadler, Romine, Stuart, and Merle-Johnson [11] revealed that digital game-based learning is more effective for average students than high-achieving students. This was further supported by Israel, Wang, and Marino [32], as their study showed that students' learning preparatory status (pretest scores, reading proficiency, etc.) could influence their learning growth in digital game-based instruction.…”
Section: B Game-based Instructionmentioning
confidence: 68%
“…Moreover, Sadler, Romine, Stuart, and Merle-Johnson [11] revealed that digital game-based learning is more effective for average students than high-achieving students. This was further supported by Israel, Wang, and Marino [32], as their study showed that students' learning preparatory status (pretest scores, reading proficiency, etc.) could influence their learning growth in digital game-based instruction.…”
Section: B Game-based Instructionmentioning
confidence: 68%
“…While experimental models and single-subject research models were considered in quantitative research methods, a case study was included in qualitative research methods. There were 11 studies using a full and quasi-experimental design with experimental and control groups (Boardman, Klingner, Buckley, Annamma, & Lasser, 2015;Botsas, 2017;Boyle, 2010aBoyle, , 2010bBoyle, 2011;Bulgren, Ellis, & Marquis, 2014;Gaddy, Bakken, & Fulk, 2008;Israel, Wang, & Marino, 2016;Lam, Doverspike, Zhao, Zhe, & Menzemer, 2008;Marino, Black, Hayes, & Beecher, 2010;McCrea Simpkins, Mastropieri, & Scruggs, 2009). There were seven studies employing single-subject research including multiple probe design, ABAB withdrawal design, AB design with regards to quantitative research methods (Aydeniz et al, 2012;Benedek-Wood, Mason, Wood, Hoffman & McGuire, 2014;Helman, Calhoon, & Kern, 2014;Kim & Linan-Thompson, 2013;Seifert & Espin, 2012;Thornton, McKissick, Spooner, Lo, & Anderson, 2015;Wills & Mason, 2014).…”
Section: Distribution Of the Research Methodsmentioning
confidence: 99%
“…İncelenen çalışmalarda nicel araştırma yöntemlerinden deneysel model ve tek denekli araştırma modelleri kullanılırken, nitel araştırma yöntemlerinden durum çalışması kullanılmıştır. Nicel araştırma yöntemlerinden deney ve kontrol gruplu tam ve yarı deneysel desen kullanılan 11 çalışma yer almaktadır (Boardman, Klingner, Buckley, Annamma, & Lasser, 2015;Botsas, 2017;Boyle, 2010aBoyle, , 2010bBoyle, , 2011Bulgren, Ellis, & Marquis, 2014;Gaddy, Bakken, & Fulk, 2008;Israel, Wang, & Marino, 2016;Lam, Doverspike, Zhao, Zhe, & Menzemer, 2008;Marino, Black, Hayes, & Beecher, 2010;McCrea Simpkins, Mastropieri, & Scruggs, 2009). Nicel araştırma yöntemlerinden tek denekli araştırma modellerinin kullanıldığı yedi çalışma yer almaktadır.…”
Section: Nitelunclassified
“…Out of the 14 articles published at Journal of Research in Science Teaching (top journal in the field), 2 studies used video games (Israel et al, ; Sadler et al, ), 10 integrated simulations (Bell & Trundle, ; Chao et al, ; Chen et al, ; Gerard, Spitulnik, & Linn, 2010; Hmelo‐Silver et al, ; Jaakkola et al, ; Mulder, Bollen, de Jong, & Lazonder, ; Plass et al, ; Quellmalz, Timms, Silberglitt, & Buckley, ; Scalise & Clarke‐Midura, ), and 2 used interactive dynamic visualizations (Ryoo & Bedell, ; Ryoo & Linn, ). The video games targeted topics such as cell anatomy and functions, genes and inheritance (Israel et al, ), and one was in the form of a virtual biotechnology lab (Sadler et al, ). Moreover, simulations included tools such as PlateTechtonics interactive simulation model of convection currents and plate movements (Gerard et al, 2010) and Energy3D, a simulated environment for designing, analyzing, and constructing green buildings utilizing renewable energy (Chao et al, ).…”
Section: Seven Emergent Technologies Used In Science Educationmentioning
confidence: 99%